Evaluasi Tata Kelola TI Layanan Sistem Informasi Akademik Tahfizh Menggunakan COBIT 5 Domain EDM - Riza Hidayat; Sopan Adrianto; Dadang Iskandar Mulyana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
With the rapid advancement of information technology, many organizations are leveraging it to support business processes, including in the education sector. Rumah Qur'an Al-Inayah in South Tangerang uses the Tahfizh Academic Information System to manage student administration. Although effective, there are still challenges, such as a lack of expert human resources, suboptimal system management, and data discrepancies. Evaluating the implementation of information technology using COBIT 5, particularly in the EDM (Evaluate, Direct, and Monitor) domain, is essential. This study employs a mixed-method approach, combining qualitative and quantitative methods. The evaluation results reveal gaps in five EDM subdomains: EDM 01 (0.58), EDM 02 (0.74), EDM 03 (0.9), EDM 04 (0.71), and EDM 05 (0.63). Recommendations include adding dedicated human resources, conducting regular maintenance, and optimizing task and access rights distribution. Implementing these recommendations is expected to improve the performance and IT governance at Rumah Qur'an Al-Inayah.